2013 ACM / IEEE International Symposium on Empirical Software Engineering and Measurement 2013
DOI: 10.1109/esem.2013.59
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Comparison of Two Safety Analysis Methods and Its Replication

Abstract: Background) Empirical Software Engineering (SE) strives to provide empirical evidence about the pros and cons of SE approaches. This kind of knowledge becomes relevant when the issue is whether to change from a currently employed approach to a new one or not. An informed decision is required and is particularly important in the development of safety-critical systems. For example, for the safety analysis of safety-critical embedded systems, methods such as Failure Mode and Effect Analysis (FMEA) and Fault Tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
(26 reference statements)
0
13
1
Order By: Relevance
“…≠ The previous elements (research goal/question/hypothesis, and statistical hypothesis) do not usually appear together in the same experiment. Jung et al [13] is one of the few cases in which the four are explicitly reported. In turn, it is rather common that one or several are missing (in particular, the research hypotheses and the statistical hypotheses).…”
Section: Review Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…≠ The previous elements (research goal/question/hypothesis, and statistical hypothesis) do not usually appear together in the same experiment. Jung et al [13] is one of the few cases in which the four are explicitly reported. In turn, it is rather common that one or several are missing (in particular, the research hypotheses and the statistical hypotheses).…”
Section: Review Resultsmentioning
confidence: 98%
“…Although unnecessary from a technical viewpoint, researchers tend to create research questions to report this refinement process explicitly. For instance, the research questions below appear also in [13]:…”
Section: Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations